The Asymmetric Impact of Context on Advantaged versus Disadvantaged Options. (April 2018) - Evangelidis, Ioannis; Levav, Jonathan; Simonson, Itamar
Despite substantial prior research regarding the effect of context on choices, uncertainty remains regarding when particular context effects will be observed. In this article, the authors advance a new perspective on context-dependent choices, according to which context effects are a function of the relative advantage of one option over another and of the different strategies that decision makers evoke when making a choice. They propose that context effects resulting from the addition of a third option to a two-option set are more frequently observed when the added option is relatively similar (adjacent) to the "disadvantaged" alternative (i.e., the lower-share option) in the set. The authors conduct a series of studies to analyze the occurrence of context effects and find support for predictions related to asymmetric dominance and extremeness aversion.